Antimicrobial photocatalysis using bio-hydrothermally synthesized Zinc oxide nanoparticles in the management of periodontitis: a prospective split-mouth, double-blind, randomized, controlled clinical trial - MATHEW, C. Afigith; VEENA, H. R.; SHUBHA, P.; DANIEL, Riya Achamma (Journal of applied oral science, 2023)
The antimicrobial activity of metallic nanoparticles (NPs) has been confirmed to fight a broad spectrum of microorganisms, through antimicrobial effects that are amplified when these particles are irradiated with light of the proper wavelength. This is the first study to use phytoconjugated Zinc oxide (ZnO) NPs containing traces of active biomolecules derived from Emblica officinalis (E. officinalis) plant extract in antimicrobial photocatalysis (PCT) during non-surgical periodontal therapy. This study aimed to evaluate the effects of repeated PCT application in the treatment of periodontitis, using a gel containing bio-hydrothermally synthesized ZnO NPs and visible light as an adjunct to scaling and root planing (SRP). In total, 16 systemically healthy volunteers with stage 3 grade B generalized periodontitis were recruited for this prospective double blind, randomized placebo-controlled trial. After receiving SRP, the subjects received the following interventions in a split-mouth design at baseline, 1 week and 1 month: Group 1 - Placebo gel + Sham PCT; Group 2 - Nano ZnO gel + Sham PCT; Group 3 - Placebo gel + PCT; and Group 4 - Nano ZnO gel + PCT. The site-specific profile of Porphyromonas gingivalis in the subgingival plaque and clinical parameters (Plaque Index, Gingival Index, Gingival Bleeding Index, Probing pocket Depth and Clinical Attachment Level) were assessed at baseline, 1 month and 3 months. All interventions tested caused participants' clinical and microbiological parameters to generally improve after 3 months. Subjects who received the Nano ZnO gel + PCT combination showed a sustained and progressive improvement in their treatment outcomes, a result that presented statistically significant differences from the outcomes obtained through the remaining interventions, at all time points during the study period. The repeated application of PCT using bio-hydrothermally synthesized ZnO NPs can effectively complement SRP in the non-surgical treatment of Periodontitis.